Address at the opening of the Thirty-eighth Session - McDonnell, James (Statistical and Social Inquiry Society of Ireland, 1885)
Before entering on the subject of my address to-night, I feel that I must thank you very heartily for the great honour you have conferred upon me in placing me in the position of president of your society. When I look over the list of eminent men who have filled this office since the commencement of your society in 1847, I confess that I enter on my duties to-night with a feeling of great diffidence. And this feeling is not lessened by the consideration that in some respects my opinions may not be in accordance with those of many of the members of this society.
Read before the Society, 2 December 1884
Keywords: 314.15